2016
DOI: 10.1002/app.44565
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated katira gum‐graft‐poly(N‐vinyl imidazole): A useful scavenger of mercury(II) ions

Abstract: Katira gum-graft-poly(N-vinyl imidazole) was synthesized in a water medium with potassium perdisulfate as the freeradical initiator at 70 6 1 8C. The graft copolymer was sulfated by chlorosulfonic acid in the presence of pyridine and formamide. Various characterization techniques, including Fourier transform infrared (FTIR) spectroscopy and field emission scanning electron microscopy, were used to characterize both the unsulfated and sulfated graft copolymers. The sulfated graft copolymer was used for the adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Adsorption or ion exchange using different polymeric materials and synthetic resins is the method of choice in many wastewater treatment processes for removing dyes or water treatment from chemical process industries in certain developed countries. Studies have been reported on the use of hydrogels or hydrophilic characteristic cross‐linked polymers or copolymers as adsorbents for the removal of dyes, the recovery of metals, the removal of toxic or radioactive elements from various effluents, and metal preconcentration for environmental sample analysis from aqueous solutions . Adsorption of some species such as dyes and heavy metal ions, desalination of sea water, ultrafiltration, and purification of aqueous solutions containing colloids, micro‐ and macroparticles, or other biochemical/physiological species in aqueous media has been studied for use in industrial and/or biotechnological processes …”
Section: Introductionmentioning
confidence: 99%
“…Adsorption or ion exchange using different polymeric materials and synthetic resins is the method of choice in many wastewater treatment processes for removing dyes or water treatment from chemical process industries in certain developed countries. Studies have been reported on the use of hydrogels or hydrophilic characteristic cross‐linked polymers or copolymers as adsorbents for the removal of dyes, the recovery of metals, the removal of toxic or radioactive elements from various effluents, and metal preconcentration for environmental sample analysis from aqueous solutions . Adsorption of some species such as dyes and heavy metal ions, desalination of sea water, ultrafiltration, and purification of aqueous solutions containing colloids, micro‐ and macroparticles, or other biochemical/physiological species in aqueous media has been studied for use in industrial and/or biotechnological processes …”
Section: Introductionmentioning
confidence: 99%
“…The general equation of Langmuir and Freundlich isotherms is given as equation (1) and (2) respectively as previously reported by Tripathi et al. truenormalCnormalenormalQnormale=normalK1normalQnormalm+4ptnormalCnormalenormalQnormalm truelnqe=lnkl+nlnCe …”
Section: Resultsmentioning
confidence: 99%
“…Biopolymers are generally non-toxic, biocompatible, and biodegradable, minimizing the potential for secondary pollution. Moreover, their flexibility allows for modifications and functionalization to improve performance and target specific contaminants [ 95 ]. This section will explore the different types of biopolymers commonly used in water treatment and their effectiveness in various processes.…”
Section: Biopolymersmentioning
confidence: 99%